Materialism and charitable giving: Can they co‐exist?. Issue 3 (4th March 2013) - Mathur, Anil
ABSTRACT It is generally believed that Western societies are more materialistic compared with other cultures. However, it has also been observed that Americans are among the most generous of all, contributing their time, money, and effort to charitable causes. This research attempted to examine the relationship between materialism and charitable giving. Results of an empirical study suggest that it is possible for materialism to co‐exist with charitable giving. Implications of the findings and suggestions for future research are also discussed. Copyright © 2012 John Wiley & Sons, Ltd.